NETFLIX: CULTURAL DIVERSITY OR CULTURAL IMPERIALISM? - Khansa Salsabila (Universitas Gadjah Mada, 2021)
The global rise of Netflix as subscription video-on-demand (SVOD) has emerged along with its capitalization of film, television, and technology industry for the audience's convenience. It replaces the interest of local television with its claim of 'a global TV network' with cultural diversity in its contents. However, the term cultural diversity itself should be questioned whether it means to leave the American cultural power or it is only to claim themselves as a global company where global identity is represented in their identity to attract a wider audience. By using transnational approach, this study finds the use of cultural diversity merely to fulfill the demand of the American audience, with several globalization consequences in Netflix Original series, especially in non-American series. Those consequences are the homogenization in European-made Netflix series, where they appear to be fully Americanized with American lifestyle or American perspective, and heterogenization in Asian-made Netflix series with its collaboration of Asian culture and American popular culture. The claim of a 'global TV network' itself does not leave the American cultural power. Instead, they are taking advantage of the cultural power to retain the existing audiences and to fascinate more audiences. Therefore, the dependency of non-American producers in relying on Netflix platform as a way to reach global audience, even the use of Americanization to their works for global audience's satisfaction, confirms the cultural power of America in its ability to bring economic advancement to other countries.